Analysis of Aspects of Legal Protection for Patients Regarding Traditional Medicine in Law Number 17 of 2023 Concerning Health - Sembiring, Tamaulina Br.; Pasaribu, Alza Hamonangan (Formosa Journal of Multidisciplinary Research, 2024)
This research examines legal protection for patients who are victims of traditional medical malpractice based on Law Number 17 of 2023 concerning Health. In the context of the increasing use of traditional medicine in Indonesia, it is important to understand existing legal protection mechanisms and how effective these regulations are in protecting patients' rights. This study uses a qualitative approach with literature study methods and analysis of related laws and regulations. The research results show that Law Number 17 of 2023 has provided a clearer legal framework in regulating traditional healing practices and provides protection mechanisms for patients. However, implementation in the field still faces various challenges, including a lack of effective supervision, limited public knowledge about their rights as patients, and differences in service quality in various regions. This research also identifies the important role of local governments in supervising and coaching traditional medicine service providers, as well as the need to increase education and outreach to the community regarding patient rights. In conclusion, although Law Number 17 of 2023 has provided a significant legal basis, there is still room for improvement in the implementation of this regulation to ensure optimal protection for traditional medicine patients in Indonesia.